Relationship between muscular and bony anatomy in native hips: a theoretical background for approach-specific implant positioning. Issue 2 (March 2019) - Akgün, Doruk; von Roth, Philipp; Winkler, Tobias; Perka, Carsten; Trepczynski, Adam; Preininger, Bernd
Introduction: The aim of this study was to analyse the relationship between bony joint orientation and the distribution of hip musculature. Methods: The bone anatomy of the hip (femoral antetorsion (AT), acetabular anteversion (AV), and combined anteversion (AV/AT)) and the muscle volume of the gluteal muscles and the tensor fasciae latae were analysed bilaterally using computed tomography data of 49 patients. Muscle force direction (MFD) was determined for each muscle. The total MFD of the hip musculature was calculated and then correlated with the bony anatomy. Results: The mean AV, AT, and AV/AT were 21.9° ± 5.9°, 7.22° ± 7.4°, and 29.2° ± 9°, respectively. We found the following mean muscle volumes: gluteus maximus: 780 ± 227 cm3, gluteus medius: 322 ± 82 cm3, gluteus minimus: 85 ± 20 cm3, and tensor fasciae latae: 68 ± 22 cm3. The mean MFD was 18.92° ± 1.29°. We found a uniform distribution of the musculature that was not correlated with the bone anatomy. Conclusion: This study highlights the variability in native acetabular and femoral anatomy and that bone hip anatomy does not correlate with the distribution of hip musculature. Although native acetabular anteversion matches the suggested targets for cup insertion, native combined anteversion is not related to current implant insertion targets. Understanding native muscular anatomy and the alterations that occur with different surgical approaches can serve as an explanatory model for THAs that has become unstable despite the components being implanted within the safe zone.